The penal rule on the blank - Alawee, Hussein; Abdullah, Kadhem (Journal of Legal Sciences, 2022)
The source, the objective penal rule that consists of two parts: crimination & penalty, the part of crimination is the (ORDER) that means the mater that has been avoided. (THE ORDER) or the order that has been done (THE PROHIBITION) , it is an order or prohibition has been enacted by the legislator to the adult person to subject to the penal rule , but the part of the penalty is the legal effect that resulted to violate the crimination part , and the source is to mention the penal rule with two parts in one penal code , but maybe to be mentioned as separated matter more than one legislative code in the law or contemporary different laws , there is one special & very accurate case to separate the penal base when the penal text contains the penal part in that base and refer to identify the crimination part to the crimination sources & the penalty to undertake this identification , and this case is called the penal base in blank. The penal base gives blank on the blank of more flexibility on the penal base within it , it is possible to those rules to go up the developments & fast changes that get benefit to society interests, where the legislator identify the penal in the general frame and the mission to identify the crimination has been left to other departments that the charge requires an artistic experience & awareness that never existed for the legislation. Therefore, he will authorize competent department to see it a suitable for the crimination upon the legal disciplines.